The importance of Social Workers Committees into the intra-hospital organ and tissue donation for transplantation. - Bandeira, Sílvia Franco Dórea; Behrens, Sandra Maria Melo (Brazilian Journal of Transplantation, 2010)
Changes in the health system have promoted changes in several areas and to health professions. As to the CIHDOTT, Social Workers have another professional field of action to develop their skills, changing from a merely ideological aspect towards a mean to assure some social rights towards a more active and innovative practice. The subject of this article aims to describe the importance of the present Social Worker as to the National Transplantation System. The methodology used was the literature review and to perform a description on the authors’ job experience in the Transplant Coordination System in the State of Bahia. It was concluded that nowadays, the health professional actuates as a mediator to families, more focused on the death / dying process serving as a supporter to the donation / transplant process. Social Workers get more room, renewing themselves in the theoretical and methodological structure and policies, inserting a new step to the social services in the health care.